PENGAWASAN PEMANFAATAN TANAH KAS DESA DI WILAYAH DAERAH ISTIMEWA YOGYAKARTA - Kartika Sari, Ika (Journal of Innovation Research and Knowledge, 2025)
Village Owned Land is land that used to support the implementation of the village government. Its use must pay attention to the principle of origin, principle of government effectiveness, and the principle of utilizing local wisdom. As the value of land increases, to maximize profits, in the provision of land for development often using procedures that do not comply with the rules, one of them uses village land without complying with the provisions. In this article, using normative legal research methods, an analysis is carried out to determine are there any existing regulations relating to the supervision of the use of Village Owned Land in the Special Region of Yogyakarta has been adequate